Peningkatan Pemahaman Investasi Berjangka Bermodal Kecil bagi Ibu Rumah Tangga untuk Kesejahteraan - Devi, Riska Sari; Zawawi, Zawawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The low level of financial literacy among housewives, particularly in understanding small-capital futures investment, remains a challenge in making safe and informed financial decisions. This community service activity aims to strengthen housewives’ financial literacy by improving their understanding of licensed futures brokers, risk principles, and mechanisms for initiating investments with affordable capital. The program was conducted offline using an educational and interactive approach, including material presentations, profit and loss calculation simulations, and open discussions. The results indicate an improvement in participants’ understanding of futures trading mechanisms, their ability to distinguish between legal and illegal brokers, and increased awareness of the potential returns and risks associated with small-capital investments. This activity also corrected the perception that investment always requires large funds, thereby encouraging more productive financial management and contributing to improved household welfare.